Korean- English Code Mixing and Code Switching Of New Jeans’s Song - Margaretta, Witness Eunike; Rangkuti, Rahmadsyah (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This paper reviewed code-mixing and code-switching along with the worldwide recognition of K-Pop songs by analyzing the English usage of "Hype Boy" and "OMG" by New Jeans, a fourth-generation K-Pop group. All songs were examined using Muysken's (2000) code-mixing theory, Stockwell's (2007) code-switching theory, and Fernandez-Martinez et al.'s (2014) and Kwon's (2019) comment analysis. The results revealed that the majority of code-mixing in "Hype Boy" was insertion and the majority of code-mixing in "OMG" was alternation, but there was no congruent lexicalization found in the two songs. However, the majority of code switches in "Hype Boy" were inter-sentential, whereas "OMG" was intra-sentential, and two tag-switching data were found. Aside from that, based on audience responses in the comment section, the audience responses showed up that they were impacted by the singers' word pronunciation errors, however, a lot were also impressed with their easy-to-listen-to songs. The study finds that the accurate pronunciation and the new English language switching function seem to have played a significant role in the success of "Hype Boy" and "OMG" among bilingual audiences.